2012
DOI: 10.1590/s1678-77572012000500008
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pre-flaring and file size on the accuracy of two electronic apex locators

Abstract: ObjectiveThis ex vivo study evaluated the effect of pre-flaring and file size on the accuracy of the Root ZX and Novapex electronic apex locators (EALs). Material and methodsThe actual working length (WL) was set 1 mm short of the apical foramen in the palatal root canals of 24 extracted maxillary molars. The teeth were embedded in an alginate mold, and two examiners performed the electronic measurements using #10, #15, and #20 K-files. The files were inserted into the root canals until the "0.0" or ''APEX'' s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 34 publications
4
13
0
Order By: Relevance
“…This increase is similar to those found in previous studies that used other EALs 15,[20][21] . This result can be due to a better adjustment of the file to the apical third 26 , promoting less exposure of metallic surface to the surrounding electrolyte and allowing the impedance reading in that region to be more effective 10 .…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This increase is similar to those found in previous studies that used other EALs 15,[20][21] . This result can be due to a better adjustment of the file to the apical third 26 , promoting less exposure of metallic surface to the surrounding electrolyte and allowing the impedance reading in that region to be more effective 10 .…”
Section: Discussionsupporting
confidence: 91%
“…According to the results obtained in this study, and also according to other similar studies, the tolerance range was adopted and allowed to observe that after cervical preparation the devices used were highly effective 21,27 . In addition, no cases of over extension were observed, which was similar to the results found by Brito Junior et al 21 .…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…The effect of pre-flaring or widening prior to determination of the WL has been studied, for example in the study of Brito-Júnior et al (2012), who assessed the performance of the Root ZX and the Novapex. This study found greater accuracy in the electronic measurements taken by the devices, both of which presented acceptable results in the palatine canals of upper molars.…”
Section: Discussionmentioning
confidence: 99%